2003
DOI: 10.1038/nbt828
|View full text |Cite
|
Sign up to set email alerts
|

Turnover-based in vitro selection and evolution of biocatalysts from a fully synthetic antibody library

Abstract: This report describes the selection of highly efficient antibody catalysts by combining chemical selection from a synthetic library with directed in vitro protein evolution. Evolution started from a naive antibody library displayed on phage made from fully synthetic, antibody-encoding genes (the Human Combinatorial Antibody Library; HuCAL-scFv). HuCAL-scFv was screened by direct selection for catalytic antibodies exhibiting phosphatase turnover. The substrate used was an aryl phosphate, which is spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…We anticipate the successful use of the combination of computational design and molecular evolution that we have described here for a wide range of important reactions in the years to come. The challenge of generating new biocatalysts has led to several successful experimental strategies [20][21][22] . In particular, the Kemp elimination comprises a well-defined model for catalysis of proton transfer from carbon-a highly demanding reaction and a rate-determining step in numerous enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipate the successful use of the combination of computational design and molecular evolution that we have described here for a wide range of important reactions in the years to come. The challenge of generating new biocatalysts has led to several successful experimental strategies [20][21][22] . In particular, the Kemp elimination comprises a well-defined model for catalysis of proton transfer from carbon-a highly demanding reaction and a rate-determining step in numerous enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Rotamer pairs with a van der Waals repulsive energy less than 2.0 kcal mol 21 and hydrogen bonding energy less than 20.5 kcal mol 21 were stored in an 'interaction graph'. Matching was carried out using histidine as the catalytic residue, iterating only over histidine rotamers in the interaction graph of His-Asp and His-Glu pairs.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction-based selection with designed compounds afforded improved small peptide catalysts with respect to both catalytic activity and folded state. We have demonstrated that the reaction-based selection using phage display libraries, which has been effectively used to generate larger protein catalysts (23,24,44), is useful for the development of small designer peptide catalysts. We have also demonstrated that the substrate specificity of the peptide catalyst for a small molecule substrate can be improved by a modular assembly strategy, i.e., covalent conjugation of a binding domain to the catalytic peptide module.…”
Section: Enaminone Formation and Reaction With An N-acyl--lactammentioning
confidence: 99%
“…It is, thus, evident that innate reactivity can be deployed to capture more highly evolved biocatalysts that conserve an essential residue for covalent catalysis (12). Mechanism-based kinetic selection may, thus, be differentiated from suicide substrate selection or similar strategies that have successfully used covalent capture (13). We previously applied this approach to selection of a diversified repertoire of human Ig variable light (V L ) and variable heavy (V H ) single-chain fragments (scFv) displayed on phage particles (14).…”
mentioning
confidence: 99%